The courageous follower standing up to & for our leaders - Chaleff, Ira. (San Francisco Ingram Publisher Services, 2009)
For every leader there are dozens of followers working closely with them. This book speaks to those followers and gives them the insights and tools for being effective partners with their leaders. It is a guide that can be kept on a bookshelf and referred to repeatedly when confronted with the challenges of supporting and, at times, correcting a dynamic leader. This new edition has been updated and expanded to speak to the widespread failures of leadership we have witnessed from 9/11 to the economic collapse. Boards of Directors, Senior Managers and staff who are loyal to the mission of their organizations, will all find the expanded edition more essential than ever to preventing and righting leadership wrongs and supporting and fostering values-based leadership efforts. The main change in the third edition will be adding a new chapter on 'The Courage to Speak to the Hierarchy'. In existing editions of the book the author asserts that proximity to the leader is a requisite for influencing the leader. But only a relative few people enjoy that proximity. What are the rest to do when orders come down that seem very ill advised? The author finds that he is increasingly coaching and training to this theme and will include guidance on how to handle such situations.
Includes bibliographical references and index.
Keywords: Organizational sociology